Physiological, Physical and Technical Demands During Sided Soccer Game Formats: a Review - Clemente, Filipe Manuel; Martinho, Diogo V.; Silva, Rui; Trybulski, Robert; Sánchez-Sánchez, Javier; Rodríguez-Fernández, Alejandro; Beato, Marco; Afonso, José (International Journal of Sports Medicine, 2025)
This meta-analysis aimed to compare the acute physiological, physical, and technical demands in soccer players during different sided game formats (1v1 to 10v10). This review included studies on soccer players with a competitive or developmental level, focusing on games with at least one comparison of sided formats. Outcomes assessed included physiological parameters (e.g., heart rate and blood lactate levels), physical demands (e.g., distance and accelerations), and technical actions (e.g., passes). The risk of bias assessment tool for nonrandomized studies of interventions (RoBANS 2) and (Grading of Recommendations, Assessment, Development and Evaluation) were used to evaluate the risk of bias and the certainty of evidence. The search across PubMed, Scopus, and Web of Science identified 2,545 records, of which 72 studies were included. Meta-analyses found that 2v2 and 3v3 formats were more physiologically intense, showing higher perceived exertion and blood lactate levels, with 3v3 also having higher heart rates. The 4v4 and 3v3 formats resulted in greater physical demands compared to the 2v2 format, with increased distances covered at various speeds, although differences were minimal beyond the 4v4 format. Smaller formats promoted ball possession, while the 3v3 format resulted in more successful shots, dribbles, and passes. In conclusion, small-sided games (< 3v3) were more physiologically demanding, mid-sized formats (> 4v4) increased locomotor demands, and smaller formats improved technical skills, although the findings should be interpreted cautiously due to study limitations.
Keywords: football; small-sided games; conditioned games; technical